2022
DOI: 10.1029/2022jc018766
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Turbidity Maximum in the Modaomen Estuary of the Pearl River, China: The Roles of Mouth Bar

Abstract: An estuarine turbidity maximum (ETM) functions as a filter and plays a key role in transporting suspended sediment. The features of ETM and their formation mechanisms vary with different types of estuaries. Their responses to morphological factors require further study. In this study, the Modaomen Estuary of the Pearl River was selected to examine the formation mechanisms of the ETM and roles of the mouth bar. Hydrodynamics, suspended sediment concentration, and sediment size distribution were measured via cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…Due to the lack of bathymetric data before and after the flood in the ME, which caused the absence of validation of morphological changes, the simulation results were compared with those of previous studies. Li et al (1993) and Jia et al (2018) showed that during the flood season, the west channel of the ME experienced slight erosion, whereas the east channel was dominated by deposition. At the central mouth bar, erosion and deposition occurred simultaneously, with deposition dominating the crest and outer slope of the mouth bar, and erosion dominating its inner slope.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…Due to the lack of bathymetric data before and after the flood in the ME, which caused the absence of validation of morphological changes, the simulation results were compared with those of previous studies. Li et al (1993) and Jia et al (2018) showed that during the flood season, the west channel of the ME experienced slight erosion, whereas the east channel was dominated by deposition. At the central mouth bar, erosion and deposition occurred simultaneously, with deposition dominating the crest and outer slope of the mouth bar, and erosion dominating its inner slope.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…Tides and currents are the power source of the mixing of seawater and freshwater, caused by the gravitational forces of celestial bodies, and they have a crucial impact on seawater intrusion (Paiva and Schettini, 2021). The effects of tides and currents on seawater intrusion include: the convective transport of currents, turbulent mixing caused by tides, and the combined effect of tides and topography leading to tidal trapping and tidal transport (Li et al, 2022). Wind also has a significant impact on seawater intrusion (Tao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%